A failure criterion incorporating the effect of depositional angle for transversely isotropic soils. (August 2022) - Liang, Jingyu; Ma, Chao; Su, Yuheng; Lu, Dechun; Du, Xiuli
Abstract: The remarkable effect of the depositional angle δ on the shear strength of transversely isotropic soils (TI-soils) has long been experimentally confirmed. However, the δ- effect under the true triaxial conditions is still difficult to be well described by existing strength criteria. This paper presents a new perspective to determine the mobilized plane based on the characteristic stress, i.e., the Characteristic Mobilized Plane (CMP), and the CMP criterion is proposed according to the strength conditions on the CMP. In order to incorporate the δ -effect into the CMP criterion, the distribution of the microstructure of the TI-soil and stress, as well as the relative orientation between the depositional plane and the CMP, are analyzed. Based on the projection of the microstructure tensor onto the normal vector of the CMP, and combined with the δ -dependence strength variation rule, a CMP-based strength parameter is proposed, which can be used to improve the CMP criterion into one for TI-soils, i.e., TI-CMP criterion. The features of the TI-CMP criterion in capturing the coupling effects of b and δ are demonstrated by analyzing the variation rule of the strength curves. The validation performed against the test results examines the excellent predictive capability of the TI-CMP criterion.